Adaptive secure network coding scheme against pollution attacks - Ming HE; Gang DENG; Hong WANG; Zheng-hu GONG (Tongxin xuebao)
The problem of pullution attacks was focused on and ASNC (adaptive secure network coding) scheme was proposed, which is an adaptive security scheme against pollution attacks in network coding systems. The proposed scheme allows participating nodes to detect polluted packets based on time and space properties of network coding. It is an innovative security scheme which can dynamically adjust the authentication strategy of participating nodes according to the security situation. In addition, ASNC scheme provides an efficient packet authentication without requiring the ex-istence of any extra secure channels. Security analysis and simulation of the scheme were also and the results demonstrate the practicality and efficiency of the ASNC scheme.